Functional significance of the TATA element major groove in transcription initiation by RNA polymerase II. - Lee, D K (1997)
The binding of TFIID to the TATA element initiates assembly of a preinitiation complex and thus represents one of the most important steps for transcriptional regulation. The fact that the TATA binding protein (TBP), a subunit of TFIID, exclusively contacts the minor groove of the TATA element led us to ask whether the major groove of the TATA element plays any role in transcription initiation or its regulation. Our results show that modifications of the major groove of the TATA element in the adenovirus major late promoter have no effect on TFIID binding affinity or on transcription in a cell-free system reconstituted with purified factors. However, major groove modifications do decrease the levels of both basal and activator-mediated transcription in unfractionated nuclear extracts, indicating that the intact structure of the major groove of the TATA element is functionally important for transcription initiation in a more physiological context.